What happens to pretrial detention after the rejection of the initiation of summary proceedings? A reconstruction of the debate - Martínez Reaño, Roberto Javier (2025)
This article analyzes the legal effects of pretrial detention following the rejection of a request to initiate summary proceedings. To this end, using a Genovese realism approach, we have reconstructed the dogmatic and judicial discourse on the matter. The aim is to show that, despite being a discussion from 2016, the issue remains relevant due to legislative changes and understandings on the matter. The analysis of the discourse of five dogmatic positions on the subject and the analysis of three judicial resolutions and Extraordinary Plenary Agreement 2-2016 were used. The criteria used to select these documents were that they directly address the issue at hand and are relevant to the legal system. Texts that deal exclusively with pretrial detention or summary proceedings were discarded. After the conceptual reconstruction, the dogmatic commitments and interpretive codes used by jurists and legal practitioners were highlighted, as well as the evaluation of the internal coherence and external resistance of the arguments.